2015
DOI: 10.1016/j.jvs.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of endovascular versus open repair in the treatment of thoracic aortic aneurysms

Abstract: Objective For descending thoracic aortic aneurysms (TAAs), it is generally considered that endovascular stents (TEVARs) reduce operative morbidity and mortality compared to open surgical repair. However, long-term differences in patient survival have not been demonstrated, and an increased need for aortic reintervention has been observed. Many assume that TEVAR becomes less cost effective through time due to higher rates of reintervention and surveillance imaging. This study investigated mid-term outcomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…32 This is not surprising considering almost 50% requiring a carotid-subclavian bypass. This not only impacted the cost, but also resulted in a 6 day median length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…32 This is not surprising considering almost 50% requiring a carotid-subclavian bypass. This not only impacted the cost, but also resulted in a 6 day median length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those reported in the literature, indicating higher perioperative mortality for OSR. 23 , 24 In 2011, Goodney et al 23 found that perioperative mortality was lower in patients undergoing TEVAR than in patients undergoing OSR for both intact TAA (6.1 vs 7.1%; P < 0.05) and ruptured TAA (28 vs 46%; P < 0.01). In the USA, Hughes et al 8 compared the results of OSR with those of TEVAR and reported that, after adjustment for preoperative comorbidities, including the presence of diabetes, the likelihood of death was reduced by 46% among patients undergoing endovascular repair compared with OSR (OR 0.54; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, endovascular repair is restricted by abnormal anatomy, especially when TAA involves the aortic arch and proximal descending aorta. 6,7 Despite great improvement in surgical repair for the treatment of TAA, up to one-third of patients cannot tolerate surgical procedures because of the high risk of complications and invasiveness. 8,9 Considering the potential limitations of surgical and endovascular repair, a deep understanding of the cellular and molecular mechanisms of TAA is necessary in the case of proximal descending aortic aneurysm.…”
mentioning
confidence: 99%